E-Learning Barriers and Opportunities in Higher Education in Saudi Arabian Universities: A Literature Review - Mutasim S. ALotaibi (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
E-learning has revolutionized higher education worldwide by providing unprecedented flexibility and improved access; however, its effective application remains hindered by multifaceted challenges, particularly within the context of Saudi Arabian universities. This study aimed to identify the primary obstacles to digital adoption while evaluating the role of faculty perspectives and theoretical frameworks in navigating these complexities. Utilizing a bibliographic review method, the study identified and synthesized relevant journal articles, reports, and reviews to provide a comprehensive overview of current knowledge and research gaps. The results classify these barriers into institutional, cultural, pedagogical, and technical categories, highlighting that effective implementation is contingent upon addressing issues such as lack of training, resistance to transformation, and insufficient technical infrastructure. In conclusion, the success of e-learning depends on a holistic synergy between robust infrastructure and faculty self-efficacy, as the application of theoretical frameworks enables universities to better understand and alleviate adoption pressures. By fostering a supportive and culturally sensitive environment, institutions can empower both teachers and students, ultimately promoting a more flexible and accessible learning experience.